Ảnh hưởng hiệp đồng của lá sắn (Manihot Esculenta Crantz), bã bia, và than sinh học (biochar) lên sự sản sinh khí methane và năng suất thú nhai lại - Lê Thụy Bình Phương (2020)
This dissertation successfully demonstrated that HCN in cassava foliage is main factor for reduction of methane production while the earlier finding could only predict the role of HCN for decreased methane. Currently, the best-known cassava foliage to feed animal is “sweet” cassava foliage with low cyanide content, my dissertation succeeds to build feeding method for “bitter” cassava foliage diet (higher cyanide content) with support of adding restricted brewers grain (4% of DM) and biochar (1% of DM) to feed cattle and goats without cause HCN toxicity. Additionally, discovery of the feeding of the bitter cassava foliage appear to modify the rumen fermentation lead to increases in nitrogen retention associated with reduced methane production, it made a part of this dissertation provided the implication for new approach of the proposed partial shift in sites of digestion (from rumen to small intestine and the cecal-colon region) that previously it is thought that only rumen fermentation has a truly symbiotic relationship with the ruminant.